Panel provides new recommendations and advice for doctors on rosacea. (1st May 2020) - Schaller, M.; Almeida, L.M.C.; Bewley, A.; Cribier, B.; Del Rosso, J.; Dlova, N.C.; Gallo, R.L.; Granstein, R.D.; Kautz, G.; Mannis, M.J.; Micali, G.; Oon, H.H.; et al.
Summary: Rosacea is a skin disease that mainly affects facial skin and eyes. It has a number of different visible signs and symptoms, or 'features'. Doctors are currently switching from a subtype approach, which specifies groups of disease features, to a phenotype approach that treats each patient as an individual with their own particular set of features. The 2019 ROSCO panel (a panel of experts) aimed to make recommendations and produce methods that help doctors use the phenotype approach with their rosacea patients. The panel was formed of 19 skin specialists and two eye specialists from around the world. They used a process to vote how far they agreed with statements on rosacea diagnosis and management. Statements with 75% agreement were recorded as recommendations. The panel recommended that doctors should discuss disease burden with patients during appointments and offered questions to help them do this. The main treatment goal should be clear skin, because it can improve many aspects of patients' lives. New descriptions of how rosacea affects the skin and eyes are provided, to help recognition of this disease. Recent research has been used to update recommendations for treating rosacea, including ways to combine treatments. The panel also developed the Rosacea Tracker tool, which doctors can use with patients to keep an ongoing record of their rosacea and its treatment, and a patient case study library to help doctors recognise common rosacea features. Altogether, these recommendations should continue supporting improvements in the care of patients with rosacea. This is a summary of the study: Recommendations for rosacea diagnosis, classification and management: update from the global ROSacea COnsensus 2019 panel.